National Dam Inspection Program. Beaver Creek Dam (SCS PA 433). (NDS I.D. Number PA 00903, DER I.D. Number 15-301) Delaware River Basin, Beaver Creek, Chester County, Pennsylvania. Phase I Inspection Report - Beck,Mary F; Frederick,John H , Jr (1980)
This report is prepared under guidance contained in the Recommended Guidelines for Safety Inspection of Dams for Phase I Investigations. The purpose of a Phase I investigation is to expeditiously identify those dams which may pose hazards to human life or property. The assessment of the general condition of the dam is based upon available data and visual inspections. Detailed investigations, testing and detailed computational evaluations are beyond the scope of a Phase I investigation; however, the investigation is intended to identify the need for more detailed studies. In reviewing this report, it should be realized that the reported condition of the dam is based on observations of field conditions at the time of inspection along with data available to the inspection team. In cases where the reservoir was lowered or drained prior to inspection, such action, while improving the stability and safety of the dam, removes the normal load on the structure and may obscure certain conditions which might otherwise be detectable if inspected under the normal operating environment of the structure. Original contains color plates: All DTIC and NTIS reproductions will be in black and white.